Funções Geradoras: Problemas E Aplicações - Ferreira, Laudelino Gomes (2018)
In this work, after introducing a brief exposition to the study of the sequences and series, an introduction was made to the ordinary generating functions. A generating function G(x) is a power series associated with a combinatorial problem. Our main aim was to apply the generating functions to solve some combinatorial problems with constraints in which the order of the objects is not relevant